Modeling, analysis, and simulation of millimeter-wave Graphene Nano-Ribbon (GNR) cylindrical coupled transmission line. (November 2019) - Zarepour, Mahdi; Abdipour, Abdolali; Moradi, Gholamreza
Abstract: This paper discusses an analytical formulation for extracting electrical parameters of the Graphene Nano-Ribbon cylindrical Transmission Line (TL), and compares the results with numerical ones obtained through analysis of the same structure using the TLM method in the mm-wave frequency range. To assess the validity of this model, our proposed numerical approach and the simulated models have been compared, and a good agreement has been obtained in this comparison.